An Analysis of Instagram Algorithms and New updates in 2022 (Trinity Journal of Management, IT & Media (TJMITM), 2022)
If you are a small company or an individual who wants an audience, then an Instagram marketplace is the right place in today’s time. We all must have seen content that is trending the content in them was not that good and these photos or videos are getting views, On the other hand, Good content creators with very good content didn’t get as many views or engagement why this happens – this is because of the algorithms. That’s why all content creators should know about the platform in which they are uploading their content and also about its algorithm and what are the things to which the algorithm gives priority.                        In this analysis, you get to know about the Instagram marketplace and how it works for the content creator and the business. The previous case study also gives data that for how many followers what should be the engagement rate and also how you can calculate engagement for your profile and the individual post also. Major updates in 2022 on Instagram and how you can use it for growing your account? By posting at the right time, using hashtags in your content, being consistent with your content, and trying to create a niche.These all are the factors for the growing healthy account. In 2022 updates it is more towards stopping the content copying by detecting the copy content and by some other factors so in the experiment and result we will find out whether it works or not and what other factors are there which can affect your reach.
Keywords: Social Media; Instagram; Algorithm; Algorithmic power; Social media Bot; Marketing strategy; Opportunities Instagram hashtags